2017
DOI: 10.12659/msm.906747
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Tendon Stem Cells in Chitosan/β-Glycerophosphate/Collagen Hydrogel on Achilles Tendon Healing in a Rat Model

Abstract: BackgroundThe aim of this study was to determine whether the local application of tendon stem cells (TSCs) with chitosan/b-glycerophosphate/collagen(C/GP/Co) hydrogel promotes healing after an acute Achilles tendon injury in a rat model.Material/MethodsNinety-six Sprague-Dawley (SD) rats were used to make an Achilles tendon defect model, then the animals were randomly divided into 4 groups consisting of 8 rats each: control group, hydrogel group, TSCs group, and TSCs with hydrogel group. At 2, 4, and 6 weeks a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 34 publications
1
24
0
Order By: Relevance
“…Recent work developing biomaterials for TSPCs showed that seeding TSPCs in fibrin gels, collagen hydrogels or engineered tendon matrix (ETM) films or gels, can induce in vitro tenogenic differentiation. In addition, these scaffolds serve as successful in vivo delivery vehicles for TSPCs into a tendon defect.…”
Section: Mechanical Stimulation and 3‐dimensional Tspc Culturementioning
confidence: 99%
See 3 more Smart Citations
“…Recent work developing biomaterials for TSPCs showed that seeding TSPCs in fibrin gels, collagen hydrogels or engineered tendon matrix (ETM) films or gels, can induce in vitro tenogenic differentiation. In addition, these scaffolds serve as successful in vivo delivery vehicles for TSPCs into a tendon defect.…”
Section: Mechanical Stimulation and 3‐dimensional Tspc Culturementioning
confidence: 99%
“…The collagen matrix produced by TSPCs in vitro also remains immature (small uniform fibrils) and mechanical properties can only approach that of embryonic tendons . However, these scaffolds support TSPC expansion, limited tenogenic differentiation in vitro, and in vivo implantation (alone or in combination with growth factor or small molecule treatments) . In general, several studies suggest that combining chemical supplementation (including growth factors such as CTGF or small molecules such as TSA) with 3D culture best enhances tenogenic differentiation and improves subsequent healing after implantation of constructs .…”
Section: Mechanical Stimulation and 3‐dimensional Tspc Culturementioning
confidence: 99%
See 2 more Smart Citations
“…Chitosan in combination with collagen has also been investigated to serve as a material for tissue engineering: addition of chitosan to bovine and salmon collagen scaffolds improved the mechanical properties by increasing the compressive strength and the swelling ratio [73]. Moreover, a rat Achilles tendon study, where a scaffold based on chitosan-β-glycerophosphate-collagen was used, demonstrated the effectiveness of this composite material for this purpose [74].…”
Section: Chitosanmentioning
confidence: 99%